Risk Management of Manganese (Mn) Contamination in Drinking Water Sources - Syafreni Annisa Ayu Putri; Sri Malem Indirawati; Taufik Ashar (Indonesian Journal of Global Health Research, 2025)
Manganese (Mn) is a heavy metal that naturally exists in the environment and can contaminate drinking water sources through anthropogenic activities, particularly in agricultural areas. Long-term exposure to Mn levels above safe limits can lead to neurological disorders in humans. This study aims to analyze the risk management of manganese contamination in drinking water sources in Langkat District, North Sumatra. A cross-sectional study was conducted on 8 samples of well water and 209 respondents. Data collection included water sampling and neurological symptom assessment using the Q18 questionnaire. Risk analysis was carried out based on concentration exposure, body weight, and daily water intake to calculate the Risk Quotien (RQ). Manganese concentrations in water ranged from 0.991 mg/L–2.809 mg/L, exceeding the Indonesian Ministry of Health threshold of 0.1 mg/L. Six respondents experienced numbness, and four experienced palpitations. Risk management analysis showed a safe body weight at 36.26–141.81 kg, the safe length of residence ranged at 23.01–58.72 years, and safe Mn concentration at 0.62–2.78 mg/L. This study provides important scientific evidence for developing risk management strategies for manganese contamination in drinking water to prevent neurological issues in Langkat Regency. Recommendations were given to improve water quality monitoring and community health education.